Development and validation of 3D MP‐SSFP to enable MRI in inhomogeneous magnetic fields. Issue 2 (6th September 2020) - Kobayashi, Naoharu; Parkinson, Ben; Idiyatullin, Djaudat; Adriany, Gregor; Theilenberg, Sebastian; Juchem, Christoph; Garwood, Michael
Abstract : Purpose: We demonstrate the feasibility of MRI with missing‐pulse steady‐state free precession (MP‐SSFP) in a 4T magnet with artificially degraded homogeneity. Methods: T1, T2, and diffusion contrast of MP‐SSFP was simulated with constant and alternate radiofrequency (RF) phase using an extended phase graph. To validate MP‐SSFP performance in human brain imaging, MP‐SSFP was tested with two types of artificially introduced inhomogeneous magnetic fields: (1) a pure linear gradient field, and (2) a pseudo‐linear gradient field introduced by mounting a head‐gradient set at 36 cm from the magnet isocenter. Image distortion induced by the nonlinear inhomogeneous field was corrected using B0 mapping measured with MP‐SSFP. Results: The maximum flip angle in MP‐SSFP was limited to ≤10° because of the large range of resonance frequencies in the inhomogeneous magnetic fields tested in this study. Under this flip‐angle limitation, MP‐SSFP with constant RF phase provided advantages of higher signal‐to‐noise ratio and insensitivity to B1 + field inhomogeneity as compared with an alternate RF phase. In diffusion simulation, the steady‐state magnetization in constant RF phase MP‐SSFP increased with an increase of static field gradient up to 8 to 21 mT/m depending on simulation parameters. Experimental results at 4T validated these findings. In human brain imaging, MP‐SSFP preserved sufficient signal intensities, but images showed severe image distortion from the pseudo‐linear inhomogeneous field. However, following distortion correction, good‐quality brain images were achieved. Conclusion: MP‐SSFP appears to be a feasible MRI technique for brain imaging in an inhomogeneous magnetic field. Abstract : Click here for author‐reader discussions